Peran Orang Tua dalam Pendampingan Belajar Anak Mata Pelajaran Pendidikan Agama Islam Siswa Sekolah Dasar - Nailatun Irsyadah; Sudadi Sudadi; Atim Rinawati (IAINU Kebumen, 2023)
This study aims to find out how the process of learning Islamic religious education for students of State Elementary School 2 Bumirejo and the role of parents in assisting learning Islamic religious education subjects (PAI) for students of State Elementary School 2 Bumirejo Kebumen. This study uses a qualitative approach by observing the learning process and also the assistance carried out by parents. Researchers act as observers in the learning process at SD Negeri 2 Bumirejo as well as mentoring carried out by parents. The research instrument used was data collection, observation, interview, documentation and data analysis techniques, namely data reduction, data presentation and then verification. The results of the study found that the PAI learning process at SD Negeri 2 Bumirejo had been carried out in three stages. While there are several parents who provide learning assistance, the forms of assistance provided are also varied.